In Vitro Infectivity Study of Cryopreserved Irradiated Intraerythrocytic Form of Plasmodium falciparum - S. Nurhayati; T. Rahardjo; D Darlina; D. Tetriana; T. Kisnanto; M. Syaifudin; D. Ramadhani (PPIKSN-BATAN, 2017)
In control human malaria infection studies using irradiated Plasmodium falciparum, the cell bank of irradiated P. falciparum infected erythrocytes is needed. The cell banking methods represent an obvious way to obtain suitable material for blood stage Plasmodium. In a cell bank development of irradiated Plasmodium infected erythrocytes, the ability to cryopreserve procedure of Plasmodium is important to recover the infectivity of irradiated Plasmodium. This study aims at evaluating the in vitro infectivity of cryopreserved irradiated intra-erythrocytic form P. falciparum. A protein profile investigation using Sodium Dodecyl Sulfate-Polyacrylamide Gel Electrophoresis (SDS-PAGE) of cryopreserved P. falciparum also conducted in this study to know the cryopreserved effect on the protein of irradiated P. falciparum. Plasmodium falciparum of 3D7 strain in human erythrocytes was maintained in invitro continuous culture. When the percentage of parasites was 10-20%, the culture was harvested and irradiated with gamma rays at a dose of 175 Gy. Irradiated P. falciparum then was mixed with cryopreserved solution and stored in -80 °C for one hour before transferred into liquid nitrogen for 20, 40 and 60 days. After being stored the irradiated P. falciparum was thawed and cultured for 20 days. The percentage of parasitaemia was enumerated by examining Giemsa stained thin blood films prepared for 20 days after initiation of culture. Results showed that storage time significantly (p<0.05) influence the percentage of parasitaemia. The cooling procedure and cryopreservation media may affect this study results. It also showed that there was insignificant difference of P. falciparum protein profile in all storage times. Overall it can be assumed that the irradiated P. falciparum still kept their infectivity after stored in liquid nitrogen for 60 days. Further study using different cooling procedure and different formula of cryopreservation media with a longer storage time should be conduct to validate this study results.